Occupational health in aviation : maintenance and support personnel - Ribak, Joseph; Rayman, Russell B.; Froom, Paul (Acdemic Press, 1995)
Although much has been written about the occupational hazards confronting the cockpit crew, very little has been written on the occupational hazards faced by aviation maintenance and ground support personnel. This book fills this void by describing those hazards, their remediation, and their prevention. This important resource describes the different exposures and hazards in the aviation industry, including those of a chemical, physical, physiochemical, biological, or psychosocial nature. Biomedical engineers, physicians, nurses, flight surgeons, and aviation medical examiners will find this book to be a useful reference.